Equity, Diversity, and Inclusion in admissions: A critical qualitative inquiry on faculty leaders’ perspectives on barriers and facilitators at a Canadian health sciences institution - Xie, Jiale; Smith, Helen GE; Hajjar, Nicole; Egan, Rylan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2026)
Background: There is an ongoing need for Equity, Diversity, and Inclusion (EDI)-focused admission reform in Canadian health sciences programs. Extensive literature on critical race Theory (CRT) and Postcolonial Theory (PCT) have provided frameworks to understand and challenge existing inequities. However, there is a lack of research regarding specific challenges and dynamics involved in the application of CRT and PCT to admissions in health professions education.Methods: This study investigates systemic factors influencing EDI-focused admission reform through the perceptions of Canadian health sciences faculty leaders. Using a critical constructivist lens informed by CRT and PCT, we conducted semi-structured interviews with six leaders and applied critical thematic analysis, which uses theories of racism, coloniality, and power, to interpretate participants’ views and institutional discourses.Results: Participants acknowledged bias in traditional admission metrics (e.g., GPA, MCAT) but continued to prefer them over equity-based alternatives, perceiving the former as better indicators of curricular and professional success. Admission reform was perceived to be a resource-intensive add-on that was difficult to prioritize. Broader societal and institutional forces, such as accreditation, peer institutions, and leadership discourses shaped support for equity initiatives.Conclusion: We conclude that the concurrent reliance on traditional measures of merit in admissions, curriculum, and practice reinforces the cultural currency of those colonial measures. Admission reform efforts should be accompanied by parallel initiatives across other academic domains and appropriate funding and regulatory support to break the self-fulfilling cycle of bias and inequity.